The DYNAMICS OF GEOLOGICAL SCIENCE IDEOLOGY IN “THOUSAND YEARS OF THE ‎FUTURE” BY TAUFIQ EL-HAKIM ‎ - sahar banu rizkita (Institute of Research and Community Service, Institute of Pesantren Kiyai Haji Abdul Chalim, 2020)
This study aims to analyze the ideological dynamics that occur in the main character named Geologist in the short story 'Thousand Years of Future' by Taufiq el-Hakim. This analysis uses Marx's theory of sociological literature which focuses on the grouping of classes of people based on infrastructure and superstructure in literary works. Exposure analysis includes; (1) discussion of ideological conceptualization, (2) discussion of Marx's sociology about the paradigm of 'Death' short stories relation to the structure of social class in society which includes: (a) analysis of the structure of literary social classes, identification of social backgrounds into the context of their occurrence, identification of social classes, analysis of social activities that occur between social classes represented in interrelated relations related, and (b) the relationship of the structure of the social class of literature with the structure of the social class of society. Based on the analysis, we found the forms, causes and impacts of the ideological dynamics of geologists on society.